Symptomatology of self-referred depression by oncological patients in times of the COVID-19 pandemic (Research, Society and Development, 2021)
Cross-sectional study carried out with cancer patients with the aim of estimating the prevalence of symptoms of self-reported depression in times of the COVID-19 pandemic. Data collection was performed using the Hospital Anxiety and Depression Scale - HADS. 108 patients with cancer diseases participated in this study. A descriptive and statistical analysis was performed to verify the association between the variables. We used the chi-square test between the variables with a significance level of 0.05. Thus, we noticed that only the variables depression and anxiety, depression and summary statistical work with p-value less than 0.05. Based on these results, a logistic regression was performed and the odds ratio was calculated between the variables depression, work and anxiety, in which we observed that people who have already worked and no longer work have a greater chance (3.36 times) of present a picture of depression. Furthermore, people with anxiety are also more likely (14.86 times) of depression.